KARAKTERISTIK HABITAT DAN DISTRIBUSI ASAM HALUBI (Eleiodoxa conferta)(Griff) Burret 1942, DESA BINANGA DUA KEC. SILANGKITANG KABUPATEN LABUHANBATU SELATAN - Rivo Hasper Dimenta; Jahrina Jahrina; Rusdi Machrizal (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
This research aims to determine the habitat characteristics and the distribution of halubi (Eleiodoxa conferta) in Binanga village, Silangkitang subdistrict of Labuhanbatu Selatan Regency. In an effort to sampling, this study using explore descriptive method. Halubi (E. conferta) found to be analyzed morphological characteristics of stems, leaves, flowers, fruit, and seeds. Measurement of physical-chemical parameters performed in situ. The distribution of halubi (E. conferta) is found 2 point in this village, with the character environment such as temperature (31-32 °c), air humidity (68-72%), pH of the soil (5,5 – 6,9), as well as the type of soil in the form of peat young and clay.